Responsiveness of voltage-gated calcium channels in SH-SY5Y human neuroblastoma cells on micropillar substrates. Issue 2 (22nd January 2018) - Wang, Wenxu; Zhong, Donghuo; Lin, Yu; Fan, Rong; Hou, Zhengjun; Cao, Xiumei; Ren, Yubin
Abstract: In this study, poly-L-lactic acid micropillar substrates were fabricated to evaluate the influence of topographic substrates on cell morphological and functional characteristics, such as spreading area, voltage-gated calcium channels (VGCCs) and membrane potential. The proliferation, spreading area, perimeter and circularity of SH-SY5Y cells interfaced with different substrates were first investigated. In addition, the cytoskeleton and focal adhesion of a cell as important manifestations of cell morphology were analyzed by immunofluorescence. VGCC responsiveness was evaluated by measuring the dynamic changes in intracellular Ca 2+ evoked by 50 mM extracellular K + . To determine study whether the differences in VGCC responsiveness were caused by the differences in VGCC gene expression, the expression of N/L- type VGCCs was determined by qPCR and fluorescence staining. Notably, improved measurement of the membrane potential with potentiometric fluorescent dye TMRM was applied to determine the membrane potential of SH-SY5Y cells. Results indicated that the SH-SY5Y cells were deformed significantly to adapt to the substrates; however, no distinct effect on the proliferative ability of SH-SY5Y cells was observed. The micropillar substrates markedly influenced VGCC responsiveness, which correlated strongly with cell spreading but not with VGCC expression. The resting membrane potential of SH-SY5Y cells cultured on different substrates also changed, but no effect on responsiveness of VGCC was observed. These results suggest that the effect of the micropillar substrates on cell VGCC responsiveness may be attributed to changes in the functionality of the ion channel itself. Thus, topographic substrates can be used to engineer cell functionality in cell-based drug screening.